Generalized analytical expressions for end-to-end throughput of IEEE 802.11 string-topology multi-hop networks - Sanada, Kosuke; Komuro, Nobuyoshi; Li, Zhetao; Pei, Tingrui; Choi, Young June; Sekiya, Hiroo (Ad Hoc Networks, 2018)
It is an effective approach for comprehending network performance is to develop a mathematical model because complex relationship between system parameters and performance can be obtained explicitly. This paper presents generalized analytical expressions for end-to-end throughput of IEEE 802.11 string-topology multi-hop networks. For obtaining expressions, a relationship between the durations of the backoff-timer (BT) decrements and frame transmission is expressed by integrating modified Bianchi's Markov-chain model and airtime expression. Additionally, the buffer queueing of each node is expressed by applying the queueing theory. The analytical expressions obtained in this paper provide end-to-end throughput for any hop number, any frame length, and any offered load, including most of analytical expressions presented in previous papers. The analytical results agree with simulation results quantitatively, which shows the verifications of the analytical expressions.
Keywords: Hidden nodes; IEEE 802.11s; Markov chain models; Multihop networks; Throughput analysis; Hidden nodes; IEEE 802.11; Markov-chain model; Multi-hop networks; Queueing theory; Throughput analysis